ARCHITECTURE OF A SOFTWARE SYSTEM FOR SOIL POLLUTION PROCESSES MODELING AS A RESULT OF DIFFUSION OF NITROGEN DIOXIDE IN SOILS AND GROUNDWATER - TYMCHYSHYN, VASYL; OTOO, FRANK (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The work proposes a software architecture that will allow simulating the processes of soil pollution due to the diffusion of nitrogen dioxide in soils and groundwater. To achieve this goal, mathematical models were used to predict the dynamics of concentrations of harmful emissions, as well as a model of diffusion of nitrogen dioxide in the soil and reservoir. The use of mathematical models will allow predicting changes in concentrations of nitrogen dioxide at a certain point of pollution. In addition, the model of diffusion of nitrogen dioxide in the soil and reservoir will help to determine the ways of the spread of pollution and its impact on the environment. Such models are based on difference equations or differential equations in partial derivatives, which allow to describe the dependence between various factors. The software architecture includes the necessary modules for entering initial conditions, performing calculations, visualizing results, and making adjustments to the model if necessary. A number of diagrams are presented that illustrate the features of interaction of system modules at the level of classes and components